Porous silicon based Bragg-grating resonator for refractive index biosensor - Sahu, S. (Springer Verlag, 2018)
In this work, we have evaluated the biosensing capability of the porous silicon (PSi) based sidewall Bragg-grating resonator. The approximation of the quasi-TE mode full vector for the eigenmode calculation is performed using a full vector mode solver. The transmission spectra of the device are evaluated using the transfer matrix method. We have observed a shift in the resonant band for a change in the refractive index of biomaterial in the upper cladding region. The theoretical value of the bulk sensitivity is calculated to be 387.48 nm/RIU. The device is suitable for biosensing application due to its ability of interacting signal with the infiltrated analytes in the PSi waveguide core.